Updated European Association of Urology Guidelines Regarding Adjuvant Therapy for Renal Cell Carcinoma - Bex, Axel; Albiges, Laurence; Ljungberg, Börje; Bensalah, Karim; Dabestani, Saeed; Giles, Rachel H; Hofmann, Fabian; Hora, Milan; Kuczyk, Markus A; Lam, Thomas B; Marconi, Lorenzo; Merseburger, Axel S; et al. (European urology, 2017)
UNLABELLED: The European Association of Urology Renal Cell Carcinoma (RCC) guidelines panel updated their recommendation on adjuvant therapy in unfavourable, clinically nonmetastatic RCC following the recently reported results of a second randomised controlled phase 3 trial comparing 1-yr sunitinib to placebo for high-risk RCC after nephrectomy (S-TRAC). On the basis of conflicting results from the two available studies, the panel rated the quality of the evidence, the harm-to-benefit ratio, patient preferences, and costs. Finally, the panel, including representatives from a patient advocate group (International Kidney Cancer Coalition) voted and reached a consensus to not recommend adjuvant therapy with sunitinib for patients with high-risk RCC after nephrectomy. PATIENT SUMMARY: In two studies, sunitinib was given for 1 yr and compared to no active treatment (placebo) in patients who had their kidney tumour removed and who had a high risk of cancer coming back after surgery. Although one study demonstrated that 1 yr of sunitinib therapy resulted in a 1.2-yr longer time before the disease recurred, the other study did not show a benefit and it has not been shown that patients live longer. Despite having been diagnosed with high-risk disease, many patients remain without recurrence, and the side effects of sunitinib are high. Therefore, the panel members, including patient representatives, do not recommend sunitinib after tumour removal in these patients.
Keywords: Indoles; Europe; indoly; Management; adjuvantní chemoterapie; lidé; Evropa; Antineoplastic Agents; Adjuvant; protinádorové látky; karcinom z renálních buněk; sunitinib; urologie; společnosti lékařské; Nephrectomy; Kidney Neoplasms; Societies, Medical; Carcinoma, Renal Cell; Urology; směrnice pro lékařskou praxi jako téma; Pyrroles; Practice Guidelines as Topic; Sunitinib; Chemotherapy, Adjuvant; nádory ledvin; Guidelines; Renal cell cancer; pyrroly; Sorafenib; nefrektomie; Humans